(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
Chemical submission consists of the administration to a person of chemical substances, usually psychotropic substances, without their consent and without their knowledge, for criminal purposes. In recent years, there has been a growing incidence of its use in sexual assaults, becoming a major public health problem, and especially violence against women, who are the main victims. However, as it is a recent practice, with few complaints from victims, and with its difficult demonstration at the clinical level, there are very few epidemiological data that reflect the current situation. Chemical submission is reaching a greater dimension, so more and more protocols and reforms are being incorporated into the law that provide help to victims. The ease of its administration, the difficulty of demonstrating the substances, and the low number of complaints that are made, make it a means increasingly used in sexual assaults; alcohol being the most used substance, also influenced by the voluntary consumption of the victim in most cases.